Respons of Giberellic Acid and Salicylic Acid Under Salt Stress on Roselle (Hibiscus sabdarifa L.) - aisar novita (Jurnal Penelitian Agrosamudra, 2017)
Salinity in the soil have a devastating effect on plant metabolism, disrupting cellular homeostasis and uncoupling major physiological and biochemical processes. This research was conducted in a greenhouse of Agriculture Faculty, North Sumatra University, Medan, from February until June 2014. The research used completely randomized design with three factors. The first factor was giberellic acid were giberellic acid (5 mg L-1) and without giberellic acid. The second factor was salicylic acid were 0 mM, 0,5 mM and 1 mM. The third factor was salinity were 0 dsm-1 and 4-5 dsm-1. The interaction of giberellic acid and salicylic acid indecate significant effect on parameter such as chlorophyll a and b and betacarotene. Interaction between giberellic acid and salt stress indicated significant effect on chlorophyll a and b and betacarotene. Interaction between salicylic acid and salt stress indicated significant effect on growth and production such as chlorophyll a and b and betacarotene. Interaction three factors of giberellic acid, salicylic acid and salt stress indicated significant effect on chlorophyll a and b and betacarotene. Thus, evaluate the respons of giberellic acid and salicylic acid under salt stress on roselle (Hibiscus sabdariffa L) helped in the tolerance of plants to salt stress.